The Using of Distance Learning (Online) to Students of SMP IT Alhijrah Bintuju - Nasution, Laswardi (Jurnal Hata Poda, 2024)
This research was carried out at SMP IT Alhijrah Bintuju. The aim of this research is to find out whether there is a significant influence of the application of distance learning techniques (online) on the ability to write procedure texts by class VII students at SMP IT Alhijrah Bintuju.This research is an experimental study with a population of class VII SMP IT Alhijrah Bintuju consisting of 1 class in which 28 students. Meanwhile, the sample for this research was class VII with a total of 28 students using total sampling techniques. The data from this research were obtained from test scores, namely a test of the ability to write procedure texts before using distance learning techniques (pre test) and a test of the ability to write procedure texts after using distance learning techniques (post test). The data obtained were analyzed using the t test formula.Based on the results of data analysis, the results obtained consist of: 1) The results of data calculations illustrate that the mean score for the ability to write procedure texts after using the distance learning technique (online) was obtained with a score of 78.04, in the "Good" category. 2) The results of data calculations illustrate that the mean score for the ability to write procedure texts before using the distance learning (online) learning model was obtained with a score of 67.68, in the "Enough" category. 3) The results of hypothesis testing obtained a value of t0 = 4.42. These results are compared with tt at degrees of freedom (df) 54 or (N1 + N2 - 2) = 28 + 28 - 2 = 54. The tt score is 2.00 at the 5% significance level. Thus, it can be concluded that t0 is greater than tt, namely = 4.42 2.0. So it can be said "there is a significant influence of the use of distance (online) learning techniques on the ability to write procedure texts by class VII students at SMP IT Alhijrah Bintuju." Keywords: Distance Learning Techniques, Online, Procedure Text, Writing